1995
DOI: 10.1159/000292320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Preoperative Oestradiol Treatment before Vaginal Repair Operation

Abstract: The objective of the study was to assess the effects of low-dose vaginal treatment with oestradiol before vaginal operation. In a double-blind randomized study including 43 postmenopausal women scheduled for vaginal repair operation for genital descensus, it was found that 7 patients suffered from concomitant urinary stress incontinence. Vagifem® (25 µg oestradiol) or placebo was administered as vaginal pessaries daily, 3 weeks prior to surgery and the clinical effects evaluated. One month postoperatively the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Estrogens are used to control the colonization of uropathogens by decreasing the vaginal pH and promoting the colonization of lactobacilli [27]. The potential role of preoperative hormone replacement therapy is also examined in some studies [28]. Although estradiol replacement in postmenopausal women may reduce the incidence of UTIs by modifying the vaginal flora [26] and by estrogen stimulation of the urethral epithelium, Mikkelsen et al showed that preoperative estradiol treatment before vaginal repair operation might reduce the incidence of bacteriuria in the immediate postoperative period but no long-lasting effects on recurrent cystitis were seen [28].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens are used to control the colonization of uropathogens by decreasing the vaginal pH and promoting the colonization of lactobacilli [27]. The potential role of preoperative hormone replacement therapy is also examined in some studies [28]. Although estradiol replacement in postmenopausal women may reduce the incidence of UTIs by modifying the vaginal flora [26] and by estrogen stimulation of the urethral epithelium, Mikkelsen et al showed that preoperative estradiol treatment before vaginal repair operation might reduce the incidence of bacteriuria in the immediate postoperative period but no long-lasting effects on recurrent cystitis were seen [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may influence morbidity, hospital stay and the speed of restitution after surgery (12,19,20). The surgical stress response, postoperative pain, immobilization and semi-starvation cause a catabolic state and organ distress, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Among women planning to undergo surgical repair for prolapse, three studies have reported on preoperative vaginal oestrogen by various methods, compared with placebo or no treatment, with a total of 111 participants. [10][11][12] Follow-up varied from 12 weeks to 3 years of postoperative surveillance. No vaginal oestrogen was given following surgery.…”
Section: Discussionmentioning
confidence: 99%